Molecular characterization and diversity analysis of some local potato (Solanum tuberosum L.) genotypes of Bangladesh by RAPD markers: Molecular characterization and diversity analysis of local potato - Islam, Md Shariful; Hoque, Md Ekramul; Alauddin, Md; Shamsuzzaman, Md (SAARC Journal of Agriculture, 2022)
Genetic identification of cultivars and varieties is useful in preserving endangered potato germplasm and planning for new breeding programs. Molecular characterization and genetic diversity of 10 local potato genotypes of Bangladesh were investigated with five RAPD primers, namely OPA-18, OPB-06, OPC-01, OPD-02 and OPW. Genomic DNA was extracted from young leaves and PCR reactions were performed with selected primers. The selected primers generated 33 distinct and differential amplified bands (size ranged from 131-1188 bp), out of which 28 were polymorphic. The percentage of polymorphic loci was valued from 33.33% to 100%. Gene frequency was ranged from 0.300 to 1 and gene diversity was from 0 to 0.70. The inter-varietal similarity indices was ranged from 42.45% to 92.67%. Pair-wise comparisons of Nei's genetic identity value was from 0.4848 to 0.9394. The highest Nei's genetic identity (0.9394) was observed in Sheel Bilati and SAU Promising Genotype-5 genotype pair. Nei's (1972) genetic distance was from 0.0625 to 0.7239. Dendrogram based on Nei's genetic distance using Unweighted Pair Group Method with Arithmetic Means (UPGMA) indicated the segregation of studied potato genotypes into two main clusters. It was found that RAPD markers are sensitive enough to identify genetic variation in a variety of germplasm, which will be helpful for choosing genetically unique germplasm in potato breeding programs. SAARC J. Agric., 20(2): 43-55 (2022)